Double cross-linked 3D layered PBI proton exchange membranes for stable fuel cell performance above 200 °C - Liang Zhang; Mengjiao Liu; Danyi Zhu; Mingyuan Tang; Taizhong Zhu; Congjie Gao; Fei Huang; Lixin Xue (Nature Communications, 2024)
Abstract Phosphoric acid doped proton exchange membranes often experience performance degradation above 200 °C due to membrane creeping and phosphoric acid evaporation, migration, dehydration, and condensation. To address these issues, here we present gel-state polybenzimidazole membranes with double cross-linked three-dimensional layered structures via a polyphosphoric acid sol-gel process, enabling stable operation above 200 °C. These membranes, featuring proton-conducting cross-linking phosphate bridges and branched polybenzimidazole networks, effectively anchor and retain phosphoric acid molecules, prevent 96% of its dehydration and condensation, improve creep resistance, and maintain excellent proton conductivity stability. The resulting membrane, with superior through-plane proton conductivity of 0.348 S cm−1, delivers outstanding peak power densities ranging from 1.20–1.48 W cm−2 in fuel cells operated at 200-240 °C and a low voltage decay rate of only 0.27 mV h−1 over a 250-hour period at 220 °C, opening up possibilities for their direct integration with methanol steam reforming systems.